Asystematic review and meta-analysis of clinical prognostic factors linked to extravesical recurrence after radical nephroureterectomy to treat upper tract urothelial carcinoma - Zhang, Guanlan; Jiang, Zhaoqiang; Chen, Jiawei; Zhao, Ying; Wang, Jianan; Liu, Jinxing; Ding, Zhenshan; Shan, Lei (Frontiers in Oncology, 2024)
ObjectiveNumerous studies have investigated predictors of intravesical recurrence following radical nephrectomy (RNU) in patients with upper urinary tract uroepithelial carcinoma (UTUC). In contrast, extravesical recurrence (EUR) has received less focus. Consequently, this study aims to evaluate the significant predictors of EUR after RNU through a systematic review of the literature and a meta-analysis.MethodologyWe conducted a computerized bibliographic search across PubMed, Embase, and Cochrane databases to identify reports that include detailed results from multivariate analyses of predictors of EUR. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the AMSTAR (Assessing the Methodological Quality of Systematic Reviews) criteria, we selected thirteen retrospective studies, each with a sample size exceeding 100 cases. Using Review Manager 5.4 software, we performed cumulative analyses of available HR and their corresponding 95% confidence intervals to evaluate potential predictors of EUR.ResultsOur findings indicate that patient-specific predictors include preoperative Ki-67 with a HR of 3.61 (P = 0.003), neutrophil-to-lymphocyte ratio with an HR of 2.20 (P = 0.0005), and glomerular filtration rate with an HR of 3.35 (P = 0.0009). Tumor-specific predictors identified were tumor stage with an HR of 4.67 (P < 0.00001), lymphovascular invasion with an HR of 2.37 (P = 0.004), and lymph node status with an HR of 2.68 (P < 0.0001). Regarding treatment-specific predictors, positive surgical margins were associated with an HR of 3.97 (P = 0.0005), and adjuvant chemotherapy was associated with an HR of 1.65 (P = 0.03).DiscussionOur study identified three significant predictors across patient, tumor, and treatment dimensions for extravesical recurrence following radical nephroureterectomy in patients with upper urinary tract uroepithelial carcinoma. We hypothesize that history of bladder cancer, platelet-to-lymphocyte ratio, and urinary cytology could also be strong predictors of post- RNU extravesical recurrence in patients with upper UTUC, assuming adequate sample size and controlled heterogeneity. This research aims to provide urological clinicians with enhanced guidance for postoperative decision-making.